Возвращение ласточки деревенской (Hirundo rustica L.) с мест зимовки - Кистяковский, А.Б.; Коткова, Л.И.; Смогоржевский, Л.А. (Вестник зоологии, 1969)
When ringing Hirudo rustica In the Black Sea reservation and Kanev environs it was established that next year from 7 to 60% of ringed birds return home. In four cases the change of place for nesting by adult birds was observed.